Effects of a strength physical exercise program in chronic lymphocytic leukemia patients on quality of life, mental health, and frailty: a randomized controlled trial study protocol - Sánchez-González, Juan Luis; Fernández-Rodríguez, Eduardo José; Méndez-Sánchez, Roberto; Polo-Ferrero, Luis; Puente-González, Ana Silvia; de Ramón, Cristina; Marcos-Asensio, Sara; Blázquez-Benito, Patricia; Navarro-Bailón, Almudena; Sánchez-Guijo, Fermín; Martín-Sánchez, Carlos (Frontiers in Sports and Active Living, 2025)
BackgroundChronic lymphocytic leukemia (CLL) is a type of cancer that affects the blood and bone marrow, and it is the most prevalent form of leukemia in adults. Many patients experience symptoms that can significantly impact their quality of life, particularly in terms of physical ability, emotional health, and fatigue. Therapeutic exercise has shown to be an effective intervention for alleviating both physical and psychological symptoms in these patients. Specifically, strength training may help address some common treatment side effects.ObjectiveThis study aims to evaluate the effects of a therapeutic exercise program, focused on frailty in patients with CLL, along with secondary objectives including impacts on functional capacity, quality of life, psychological status, sleep quality, body composition, anthropometric variables, lipid profile and on proteins related to the immune system and inflammation.MethodsAn open label, randomized controlled trial will be carried out with 36 participants, divided into an intervention group (supervised resistance training twice a week and home exercises) and a control group (home exercise only). The primary outcome measure is fraility, assessed using Short Physical Performance Battery (SPPB). Secondary outcomes include assessments using HADS, FACT-F, EORTC QLQ-C30, EORT QLQ-CLL17.Results and conclusionsThis study will explore how physical exercise can improve quality of life and various health metrics in patients with CLL. By creating customized exercise protocols, the research seeks to boost patient well-being, improve treatment outcomes, and lessen debilitating side effects, ultimately promoting the integration of physical activity into routine care.Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT06654206).